Fuzzy analytical hierarchy process extent analysis for selection of end of life electronic products collection system in a reverse supply chain - Shumon, M.R.H.; Ahmed, S.; Ahmed, S. (SAGE Publications, 2016)
The main purpose of this study is to propose a multi-criteria model for selection of end-of-life electronic products (ewaste) collection system in a reverse supply chain. The pertinent criteria for such decision analysis and selection are determined through an extensive literature review and a questionnaire survey method. On collection systems, a few alternatives are considered for evaluation. Subsequently, fuzzy analytical hierarchy process rating method is used to evaluate the priorities of the criteria and the alternatives. Finally, global weights of the criteria and evaluation score of the alternatives are combined to get the final ranking of the collection systems evaluated. The result demonstrates the relative importance of the criteria for evaluating the alternative collection systems. Also, a real application substantiates the preference of collection system(s) to be selected. The use of this newly proposed fuzzy analytical hierarchy process analytical model indicates that decision-makers can use it to determine the appropriate collection system(s) from a set of available options in a given place or country, where cultural and other parameters are varied. Moreover, this model guides the decision process to be systematic and helps reduce considerable amount of efforts needed conventionally by using the criteria weights generated by fuzzy analytical hierarchy process approach.